Functions of miRNAs during Mammalian Heart Development - Yan, Shun (Int J Mol Sci, 2016)
MicroRNAs (miRNAs) play essential roles during mammalian heart development and have emerged as attractive therapeutic targets for cardiovascular diseases. The mammalian embryonic heart is mainly derived from four major cell types during development. These include cardiomyocytes, endocardial cells, epicardial cells, and neural crest cells. Recent data have identified various miRNAs as critical regulators of the proper differentiation, proliferation, and survival of these cell types. In this review, we briefly introduce the contemporary understanding of mammalian cardiac development. We also focus on recent developments in the field of cardiac miRNAs and their functions during the development of different cell types.